2018
DOI: 10.2147/opth.s157738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macular thickness by optical coherence tomography measurements after uneventful phacoemulsification using ketorolac tromethamine, nepafenac, vs a control group, preoperatively and postoperatively

Abstract: PurposeTo analyze, using optical coherence tomography, the macular thickness values of patient groups using nonsteroidal anti-inflammatory drug (NSAID) eye drops or artificial tears during uncomplicated cataract surgery.MethodsA total of 77 eyes from 42 patients were analyzed. The patients were divided into three groups, each using one of the following ophthalmic sterile suspensions: nepafenac (21 eyes), propylene glycol (24 eyes), or ketorolac tromethamine (32 eyes).ResultsThe mean macular thicknesses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Our study yielded the same results in which the change in mean macular thickness (centre & cube) was more in the NSAID group and was statistically significant Similarly, nepafenac group patients had a lower visual acuity decrease of more than five letters than the vehicle group. Stock RA 14 and colleagues compared the effects of nepafenac and ketorolac on macular thickness after cataract surgery. Their study yielded no difference between pre and post-operative macular thickness with the use of either drug or between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our study yielded the same results in which the change in mean macular thickness (centre & cube) was more in the NSAID group and was statistically significant Similarly, nepafenac group patients had a lower visual acuity decrease of more than five letters than the vehicle group. Stock RA 14 and colleagues compared the effects of nepafenac and ketorolac on macular thickness after cataract surgery. Their study yielded no difference between pre and post-operative macular thickness with the use of either drug or between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ticly FG, et al (29) through a randomized trial of 81 patients to study the prophylactic use of ketorolac tromethamine after cataract surgery for up to 5 weeks, with 44 in the placebo group and 37 in the ketorolac group, showed that the incidence of angiographic CME was 2/44 (4.5%) in the control group and 2/37 (5.4%) in the ketorolac group, there was no evidence of CME in these patients on OCT analysis. A comparative study by Stock RA, et al (30) of macular thickness by optical coherence tomography measurements after uneventful phacoemulsification using ketorolac tromethamine, nepafenac, vs a control group, preoperatively and postoperatively concluded that there is no significant differences in macular thickness were observed between the patient groups using two types of NSAIDs or between those groups and the control group that used propylene glycol, indicating that neither drug was superior to the other or the placebo. However, a slight macular thickening, without reduction of visual acuity, was observed in all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Miyanaga et al documented that 2 months' use of topical NSAIDs, different topical steroids, or alternating steroids and NSAIDs had no significant differences [51]. Stock et al suggested no differences between nepafenac, control, and ketorolac through 45-day follow-up [58].…”
Section: Clinical Trials Using Ophthalmic Nsaids To Prevent Postoperamentioning
confidence: 99%